Triple hormone-receptor assay: a more accurate predictive tool for the treatment of advanced breast cancer? - Barnes, D. M. (Nature Publishing Group, 1979)
In a group of 74 patients with advanced metastatic breast cancer, 57% of those with cytoplasmic oestrogen receptor activity in their tumours (REC+) showed a clinical response to endocrine therapy. Of 51 patients whose tumour was assayed for both REC and cytoplasmic progesterone (RPC) activity, 9/12 patients with REC+ RPC+ tumours responded to hormone treatment, whereas only 3/30 patients with REC-RPC-tumours had a clinical response. In a group of 19 patients in whom nuclear oestrogen receptor (REN) was also estimated in the pellets from tumour-tissue homogenates, 5/6 with tumours positive for all 3 receptors showed a clinical response. None of the 9 patients with triply negative tumours responded. Addition of the REN assay appears to reinforce the greater precision of prediction when RPC as well as REC are estimated in breast tumours.